The effect of class absenteeism on students performance: evidence from Faculty of Accountancy UITM Sabah / Emelia A. Girau, Marius Benedict and Yvonne Joseph Ason - A. Girau, Emelia; Benedict, Marius; Joseph Ason, Yvonne (Research Management Institute (RMI), 2011)
The main objective of this study is to examine the relationship between students’ attendance and academic performance. The overall results of the study showed that there is an evidence to support the hypotheses being developed for this study. The results show that there is a significant positive relationship between attendance to class and student’s performance. This indicates that students who come to class more frequently will have better result. This also indicates that UiTM existing policy on student’s attendance to class has been implemented efficiently. Thus the findings of this study provide additional insight on the importance of imposing compulsory attendance among students. It indicates that students need to attend all classes or lectures in order to get good performance during final exam.